PKCiota Inhibits the Ferroptosis of Esophageal Cancer Cells via Suppressing USP14-Mediated Autophagic Degradation of GPX4 - Hao Tao; Sheng-Jie Song; Ze-Wen Fan; Wen-Ting Li; Xin Jin; Wen Jiang; Jie Bai; Zhi-Zhou Shi (MDPI AG, 2024)
Esophageal squamous cell carcinoma (ESCC) is one of the most frequent malignant tumors, and the mechanisms underlying the anti-ferroptosis of esophageal cancer cells are still largely unclear. This study aims to explore the roles of amplified protein kinase C iota (PKCiota) in the ferroptosis of ESCC cells. Cell viability, colony formation, MDA assay, Western blotting, co-IP, PLA, and RNA-seq technologies are used to reveal the roles and mechanisms underlying the PKCiota-induced resistance of ESCC cells to ferroptosis. We showed here that PKCiota was amplified and overexpressed in ESCC and decreased during RSL3-induced ferroptosis of ESCC cells. PKCiota interacted with GPX4 and the deubiquitinase USP14 and improved the protein stability of GPX4 by suppressing the USP14-mediated autophagy-lysosomal degradation pathway. PKCiota was negatively regulated by miR-145-5p, which decreased in esophageal cancer, and also regulated by USP14 and GPX4 by a positive feedback loop. PKCiota silencing and miR-145-5p overexpression suppressed tumor growth of ESCC cells in vivo, respectively; even a combination of silencing PKCiota and RSL3 treatment showed more vital suppressive roles on tumor growth than silencing PKCiota alone. Both PKCiota silencing and miR-145-5p overexpression sensitized ESCC cells to RSL3-induced ferroptosis. These results unveiled that amplified and overexpressed PKCiota induced the resistance of ESCC cells to ferroptosis by suppressing the USP14-mediated autophagic degradation of GPX4. Patients with PKCiota/USP14/GPX4 pathway activation might be sensitive to GPX4-targeted ferroptosis-based therapy.